(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Each speaker (author of the text) has his own perception of the event taking place in reality, imagining it in a certain space, time zone, and gives a linguistic dress to the logical imagination that is formed. Linguistic realization and content formation is associated with the "counting head" chosen by the author of the speech, that is, the placement of the ongoing event in the space-time space. Hence, in speech activity there is always a need to connect the linguistic form with reality and to express a personal attitude towards it. The execution of the same tasks is the responsibility of the deictic means